Hubungan personal hygiene dengan kejadian penyakit dermatitis - Amanda, Meidia; Andini, Sandra; Erwin, Tubagus (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Dermatitis is a chronic inflammatory skin disease (recurring and disappearing), caused by external or internal stimuli. Skin exposed to dermatitis appears spotted and bubbling on its surface like boiling water bubbles. This condition is characterized by itching, redness, scaling and blistering. Purpose: To determine the relationship between personal hygiene and the incidence of dermatitis. Methods: Quantitative research type with analytical survey design and cross-sectional approach. The population in this study were Dermatitis patients who visited Kotabumi II Health Center. The sample in this study amounted to 79 respondents with non-probability sampling technique. Data collection using questionnaire sheets and observation sheets. Results: Most respondents experienced severe dermatitis, amounting to 50 respondents (63.3%). The results of the chi-square statistical test obtained a p-value of 0.000 (<0.05). Conclusion: There is a significant relationship between personal hygiene and the incidence of dermatitis. Keywords: Dermatitis; Dermatitis Disease Occurrence; Personal Hygiene. Pendahuluan: Dermatitis adalah penyakit peradangan pada kulit yang bersifat kronis (hilang timbul), akibat rangsangan dari luar maupun dari dalam tubuh. Kulit yang terpapar dermatitis tampak berbintik dan menggelembung pada permukaannya seperti buih air mendidih. Kondisi ini ditandai dengan rasa gatal, kemerahan, bersisik dan melepuh. Tujuan: Untuk mengetahui hubungan personal hygiene dengan kejadian penyakit dermatitis. Metode: Jenis penelitian kuantitatif dengan rancangan survey analitik dan pendekatan cross-sectional. Populasi dalam penelitian ini adalah pasien Dermatitis yang berkunjung ke Puskesmas Kotabumi II. Sampel dalam penelitian ini berjumlah 79 responden dengan teknik non-probability sampling. Pengumpulan data menggunakan lembar kuesioner dan lembar observasi. Hasil: Sebagian besar responden mengalami mengalami dermatitis berat yang berjumlah 50 responden (63.3%). Hasil uji statistik chi-square memperoleh nilai p-value 0,000 (<0,05). Simpulan: Terdapat hubungan bermakna antara personal hygiene dengan kejadian penyakit dermatitis. Kata Kunci: Dermatitis; Kejadian Penyakit Dermatitis; Personal Hygiene.